Using Augmented Reality for Disaster Mitigation Education in a Natural Disaster Response School - Fitri, Elsi Adelia; Arni, Yusni; Listiono, Arsella Eko; Romawina, Demi (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2025)
Indonesia has a high potential for disasters, especially in coastal areas, so disaster awareness and preparedness need to be instilled early on. One effective way is through Augmented Reality (AR)-based education. This study analyzes the use of AR media as a source of science learning integrated with natural disaster mitigation. The method used is descriptive with qualitative and quantitative approaches. Participants consisted of 58 fifth grade students in South Sumatra. Data were collected through observation, questionnaires, teacher interviews, and analysis of teaching materials. The results of the study indicate that the topics of earth relief, plate movement, and environmental factors can be integrated into disaster mitigation. Students showed interest in AR, teachers supported the use of AR in learning. In conclusion, AR has a positive impact on student understanding, engagement, and disaster preparedness, and has the potential to be an interactive learning medium. Theoretically, this study contributes to science learning by integrating natural disaster mitigation using AR, especially for abstract concepts. Practically, these findings support the development of AR-based learning media to improve natural disaster preparedness. The application of AR integrated with natural disaster mitigation is still rarely explored in previous studies, especially in science learning